(untitled) (Research, Society and Development, 2020)
Every year, thousands of people worldwide die from exogenous poisonings and it is estimated that these cases have a reasonable impact on the number of emergency services. In Brazil, different studies have directed the high mortality rates due to intoxication in the Northeast, and the state of Pernambuco has been a leader in the number of reports of exogenous intoxications. Thus, the study aimed to investigate the epidemiological and clinical profile of intoxication cases reported of the State of Pernambuco in the year 2017 and compare them to national data. An ecological study was conducted based on the extraction of data available in the SINAN for cases of exogenous intoxication in Brazil and in the state of Pernambuco, in the year 2017. The majority of cases reported in the state of Pernambuco were women (54%), adults aged 20-59 (51%), and brown color (89%). The main toxic agent was the drugs and the main circumstance was the suicide attempt. The profile of the cases in the state was similar to the national data, except for the skin color and the criterion of confirmation of intoxication, but the intoxication rate per thousand inhabitants was 60% higher than the Brazilian rate.